Effects of a Comprehensive, Multiple Risky Behavior Prevention Program on High School Students. (8th September 2016) - Collier, Crystal; Onwuegbuzie, Anthony J.; LaChapelle, Alicia; Davison, Jessica
Abstract : The purpose of this research study was to examine the effect of a multiple risky behaviors prevention program applied comprehensively throughout an entire school system involving universal, selective, and indicated levels of students at a local private high school during a 4-year period. The noncurriculum prevention program was created based upon the key elements of effective prevention programming and the need to address the growing variety of risky behaviors that the youth face today. Results (n = 469 to 614) indicated that 7 out of 15 risky behaviors statistically significantly decreased throughout the 4-year study, with 6 behaviors involving alcohol and drugs. However, many of the targeted non-substance-use risky behaviors displayed inconsistent prevalence rate patterns without statistically significant changes. These findings indicate that the frequency and intensity of programming for non-substance-use behaviors should be increased to a value at least equal to that of the substance-use behaviors. Implications for schools, prevention specialists, and future program development and research are discussed.